Review of High-Frequency High-Voltage-Conversion-Ratio DC-DC Converters - Guan, Yueshi; Cecati, Carlo; Alonso, J. Marcos; Zhang, Zhe (IEEE journal of emerging and selected topics in industrial electronics (Print), 2021)
The development of high-frequency power converters is continuously improving their power density, efficiency and fast dynamic response. Among them, high-voltage-conversion-ratio (HVCR) dc-dc converters are widely used in high gain, i.e., step-up/-down or bidirectional applications, such as power supply for data center, dc micro-grids, electrical vehicle charging systems, etc. In this article, the current main high-frequency HVCR dc-dc converters are classified into inductive-based and capacitive-based approaches, which can then be described further by four kinds in detail, namely transformer-based, coupled-inductor-based, and switched-capacitor-based, as well as combination of coupled inductor and switched capacitor. A comprehensive analysis and comparison is given, which can provide guidance for proper topology selection and further topology optimization.